Deep anterior chamber depth may be a risk factor for axial length growth in children - Huijie Cao; Huijie Cao; Yongguo Xiang; Yongguo Xiang; Hong Cheng; Hong Cheng; Kexin Sun; Kexin Sun; Shijie Zheng; Shijie Zheng; Miaomiao Du; Miaomiao Du; et al. (Frontiers in Medicine)
ObjectiveTo investigate and evaluate the progression of myopia and associated factors of axial length (AL) growth among children in Chongqing.MethodsThis six-month prospective study was conducted on students in grades 1 to 8 at a school in Chongqing, China. All participants underwent a standard ophthalmologic examination including uncorrected visual acuity (UCVA), noncycloplegic refraction, AL, and corneal topography in March 2023. Six months later, the above examinations were repeated to obtain follow-up data. Visual habits questionnaire was gained to analyze the correlation between the AL growth and vision-related behavior.ResultsA total of 417 students from Chongqing were enrolled in this study. The myopia prevalence was higher in follow-up (38.6%) than in baseline (33.3%) and the AL was longer in follow-up than in baseline (23.69 ± 1.03 mm vs. 23.57 ± 1.03 mm, p < 0.001). The anterior chamber depth (ACD) in students with AL growth greater than or equal to 0.2 mm (3.16 ± 0.23 mm) was deeper than that in students with AL growth less than or equal to 0.05 mm (3.02 ± 0.28 mm, p = 0.001), lens thickness (LT) was thinner (3.29 ± 0.10 mm vs. 3.33 ± 0.10 mm, p = 0.004). Furthermore, ACD was positively correlated with AL growth. (r = 0.181, p < 0.001).ConclusionCompared to SE, AL serves as a more sensitive indicator for monitoring myopia progression. ACD was positively correlated with AL growth, and deeper ACD may be contributed to longer AL growth.